2009
DOI: 10.21608/jpp.2009.117134
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Two Sugar Beet Varieties as Influenced by Nitrogen Fertigation Regimes Under Drip – Irrigation System

Abstract: Two field experiments were conducted on sandy soil at El-Kassasien Research Station Ismaillia Governorate, under drip-irrigation system , during the two successive seasons of 2004/2005 and 2005 /2006 to study the influence of N fertilizer application methods (7 N fertigation treatments) on yield and quality of two sugar beet varieties (Atose poly and Loados). A split-plot design technique was used to carry out this trial. The 7 N fertigation treatments were : Fr1: Applying the N fertilizer through soil + 3 hrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Differences among sugar beet varieties for LAI, top and root fresh and dry weight and total dry weight were also detected by Mohamed (2008). Ouda (2009) showed that root length and diameter of the variety Lados were significantly higher than Athose poly. Also, Al-Labbody (2003) found differences among sugar beet varieties in root length and diameter.…”
Section: Effect Of Varietiesmentioning
confidence: 94%
“…Differences among sugar beet varieties for LAI, top and root fresh and dry weight and total dry weight were also detected by Mohamed (2008). Ouda (2009) showed that root length and diameter of the variety Lados were significantly higher than Athose poly. Also, Al-Labbody (2003) found differences among sugar beet varieties in root length and diameter.…”
Section: Effect Of Varietiesmentioning
confidence: 94%
“…El-Hinnawy et al (2003) showed that the genotypes significantly differed in root and sugar yields. Also, Ouda (2009) evaluated two sugar beet varieties (Athos poly and Lodos) and reported that, Lodos variety surpassed Athos Poly in top, root and sugar yields.…”
Section: Effect Of Varietiesmentioning
confidence: 99%
“…Sugar beet variety KWS-9422 gave the highest root and sugar yields. Ouda (2009) tested two sugar beet varieties (Athos poly and Lados) and found that, Lodos variety surpassed Athos Poly in top, root and sugar yields. On the other hand, Omar (2007) indicated that sugar beet varieties had no significant effect on root and sugar yields in two seasons.…”
Section: Introductionmentioning
confidence: 99%